Asymmetrical p-stranding - Rodrigo Delgado; Bryan Koronkiewicz (Isogloss)
This study investigates the availability of preposition stranding (p-stranding) in intrasentential code-switching (CS) among US heritage speakers of Mexican Spanish. P-stranding is allowed in English, but in Spanish the preposition is traditionally pied-piped with the DP. Law (2006) argues Spanish is subject to a syntax-morphology-interface condition, which prevents the extraction of a DP from a PP due to D-to-P incorporation. Previous research has suggested that such incorporation depends upon the features inherent to the preposition, with p-stranding only accepted with Spanish-to-English switches (Koronkiewicz, 2022). We expand on that study since it only included one preposition (with/con). Furthermore, it did not explicitly test pied-piping, nor did it include matrix wh-questions, a common context for p-stranding.  Results from a written acceptability judgment task show that the participants: (i) dispreferred p-stranding in Spanish compared to pied-piping; and accepted p-stranding in English more than pied-piping. As for CS, they dispreferred p-stranding for English-to-Spanish compared to pied-piping, while for Spanish-to-English it was the inverse. Overall, these asymmetrical p-stranding results align with previous findings (Koronkiewicz, 2022) further suggesting that it is the language of the preposition that dictates incorporation.